Future Role of Exotic Tree Species in Hungarian Built Heritage Environments - Máté Sárospataki; Patrícia Szabó; Albert Fekete (Land, 2022)
Although some exotic tree species, new to the country at the time, had already been introduced at the turn of the 18th and 19th century in the Hungarian landscape gardens, using foreign tree species in the space composition became widely popular only from the second half of the 19th century. This research focused on determining the date of appearance and compositional role of exotic trees in Hungarian landscape gardens. We can still find aged exotic woody taxa which determine the historical spatial structure in numerous landscape gardens nowadays. The nationwide distribution of these species, and their location within the gardens, can be an important addition to the questions of the revitalization of historical gardens, the more so because they may be indicative of the climate adaptability and, therefore, resilience of built heritage environments. An experimental approach to the introduction and use of new exotic tree species in historic gardens where this approach can be proven to have existed is also discussed as an opportunity to use these gardens in search of new foreign taxa to adapt to climate change.